Nathalie LaCoste, Waters of the Exodus - Targoński, Mateusz Jan (The Biblical Annals, 2019)
Book Review: Nathalie LaCoste, Waters of the Exodus. Jewish Experiences with Water in Ptolemaic and Roman Egypt (Supplements to the Journal for the Study of Judaism 190; Leiden – Boston: Brill 2018) (Mateusz Jan Targoński)